Perubahan Sistem Kelestarian Air Tanah di Cekungan Air Tanah Wates Akibat Pembangunan Bandara Internasional Temon Kabupaten Kulonprogo DIY - Purwanto Purwanto; Arif Rianto Budi Nugroho; Intan Paramita Haty (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
Underground water is a component in the hydrological cycle, formed by rainwater that seeped into thesoil and flows through the media layer of rock (aquifer) in groundwater basin. Wates basin’sgrounwater includes the Wates District, Temon, Panjatan, Lendah, Brosot, a little part of the DistrictSentolo and Pengasih located in Unit Plateau of volcanics fluvio, beach units and sand dunes with thealluvial material consisting of sand, gravel, silt, and clay, flat morphology, relatively lithology andgroundwater characteristics. This lithology is potential with the occurrence of groundwaterconservation system changes, if there is excessive ground water extraction in the region which can becharacterized by the increase in salinity in ground water. The main objective of this study is to assessthe full qualitative and quantitative groundwater in the Basin Groundwater Wates International Airportdue to Temon airport construction in relation to maintaining the sustainability of groundwater systems.The methods in this study consists of several steps, starting from observation and rock’s/soildiscribtion include: measurement of rock bedding, measurement of geological structural elements,observation of morphological conditions, and sampling soil / rock to be tested in laboratory about thecontent of the mineralogy, texture and structure. Observation of surface water and groundwater isdone by testing the physical properties of the surface water include: smell, taste, turbidity, temperature(T), acidity (pH), electrolit conductivity (EC), and taking water samples to be tested in the laboratory todetermine the elements it contains a chemical that results will be used to created Diagrams Stiff andTrilinier. Estimation of resistivity (geoelectric) was conducted to determine the condition of the soil/rockbelow the surface to a depth of more than 75 m, with the aim to determine the configuration of theaquifer both laterally and vertically, the results of which will provide an overview/three-dimensionalcross-section of the local groundwater system deposits carefully situations and recharge area. Thecross-sectionwill shown information quantity/amount of groundwater and the identification of the coasttowards the potential intrusion of sea water. The results of mineralogical analysis of rocks andhydrochemical groundwater will provide information on the distribution of groundwater quality. Thisquality conditions will certainly change with the start of construction of the airport and afterconstruction of the airport. Information about the mineralogical content of rocks, hydrochemicalcontent of water and aquifer configuration will be able to contribute to efforts in the area ofgroundwater International Airport Temon, DIY.